KONTRIBUSI PENEMPATAN, KETERAMPILAN DAN PEMBERDAYAAN PEGAWAI TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS PERIKANAN KABUPATEN LAMPUNG UTARA - Ratnasari, Tuti (Jurnal Manajemen Magister Darmajaya, 2015)
The purpose of this study was to determine the contribution placement, skills and empowerment of employees on work performance of employees at the Department of Fisheries of North Lampung either partially or simultaneously. Issues raised in this study are: 1) Is staffing contribute to employee job performance in Department of Fisheries Nort Lampung Regency? 2) Is the employee skills contribute to work performance of employees in Department of Fisheries Nort Lampung Regency? 3) Is the employee empowerment contributes to employee job performance in Department of Fisheries Nort Lampung Regency? and 4) Is the placement, skills and empowering employees jointly contribute to the work performance of employees in Department of Fisheries Nort Lampung Regency? This research is a quantitative study to test the hypothesis, in which the independent variables consist of staffing, employee skills, and employee empowerment, while the dependent variable is the performance of the employee. The sample used in this study amounted to 46 employees. The results of this study indicate that the placement of employees accounted for 22.47% of the work performance of employees in Department of Fisheries Nort Lampung Regency. Employee skills accounted for 44.49% of the work performance of employees in Department of Fisheries Nort Lampung Regency. Empowering employees accounted for 33.87% of the work performance of employees in Department of Fisheries Nort Lampung Regency. Staffing, employee skills, and employee empowerment together accounted for 62.30% of the work performance of employees in Department of Fisheries Nort Lampung Regency.Keywords: Placement of Employees, Employee Skills, Employee Empowerment, Employee Job Performance